Prototype Alat Monitoring Dan Kontrol Penyiraman Tanaman Cabai Berbasis Internet of Things (IoT) Dan Android - Martani, Ahmad; Perdana, Ayu Lestari; Anugrah, Muh (Universitas Pancasakti, 2025)
Chili is a very important vegetable commodity in everyday life. The purpose of the researcher is to design a prototype of a chili plant watering monitoring and control tool based on the Internet of Things (IoT) and Blynk to make it easier for chili farmers to monitor and control the watering of chili plants remotely. The research method uses Research and Development (R&D), which aims to produce certain products and test their effectiveness. The results of this tool prototype use acrylic as a container to unite various tool components and other supporting components. The soil moisture sensor is used to detect soil moisture. The DHT11 sensor is used to detect air humidity. The DS 18B20 sensor is used to detect soil temperature. The PIR Motion sensor is used to detect objects. Information about the measurement results on the sensor will be displayed on the LCD screen and the Blynk application. DC water pump is used to remove water from the container and spray it on the plants. The test results of the Prototype concluded that the process of watering is automatic when the measurement results of the soil moisture Threshold are SP Low 40%, SP High 60%, and Temperature High 31o C, meaning that the watering process occurs when the humidity is <40% and the soil temperature <31oC and stops when the humidity is > 60%.